The Aramaic Construction qaṭlēh l-malkā ‘He Killed the King’ Aramaic Syntax in Ethiopic? - Hopkins, Simon (Journal of Semitic studies, 2022)
Aramaic and Ethiopic share highly characteristic proleptic constructions, e.g. the direct object periphrasis of the type qaṭlēh l-malkā and qatalo la-nǝguś respectively, each meaning ‘he killed the king’. The presence of such structures in Ethiopic has been held to reflect the alleged influence of Aramaic-speaking missionaries in the translation of the Bible into Ethiopic. The present article shows that, even if such missionaries were involved in the work of translation, the proleptic constructions of Ethiopic are not imported from Aramaic, but are native to the language. The striking similarity is not due to foreign influence but to independent development.